PERAN STRUKTUR MODAL SEBAGAI MEDIATOR ANTARA PERTUMBUHAN PERUSAHAAN DAN NILAI PERUSAHAAAN - Yunita, I Gusti Putu Ayu Ona; Sri Artini, Luh Gede (E-Jurnal Manajemen, 2019)
Company value is an important indicator in assessing the performance of a company. The size of a company's value can affect investors in making investments. The purpose of this study was to determine the significant influence of company growth and firm value, the influence of capital structure and firm value, the influence of company growth and capital structure, and to know the company's growth and company value mediated by capital structure. This research was conducted on consumer goods industry companies listed on the Indonesia Stock Exchange for the 2014-2016 period. The number of samples used is 26 companies using purposive sampling method. This study uses path analysis techniques (path analysis). Based on the analysis that has been found that the growth of the company has a positive and not significant effect on firm value, capital structure has a positive and not significant effect on firm value, company growth has a positive and significant effect on capital structure and capital structure capable of mediating the influence of company growth on firm value. Keywords : capital structure, company growth, company value